Studies on the variability of Rhizoctonia solani Kuhn. infecting rice cowpea abd amaranth - Haritha J Kumar (Department of Plant Pathology, College of Agriculture, 2020)
ABSTRACT Rhizoctonia solani is a ubiquitous destructive pathogen causing severe damage in economically important crops like rice and cowpea; and several vegetables like amaranth. In this context, the research work entitled “Studies on the variability of Rhizoctonia solani Kuhn. infecting rice, cowpea and amaranth.” was undertaken in the Department of Plant Pathology, College of Agriculture, Vellayani during the year 2018-2020, with the objective to study the cultural, morphological, pathogenic and molecular variability of R. solani infecting rice, cowpea and amaranth in Southern Kerala. R. solani infected samples of rice, cowpea and amaranth were collected from two locations each from the three southern districts of Kerala viz., Vellayani and Chirayinkeezhu from Thiruvananthapuram; Kottarakkara and Pooyappally from Kollam; and Thiruvalla and Ranni from Pathanamthitta. Eighteen isolates of R. solani were obtained for the study. TRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulenTRR1 (Vellayani) was more virulen TRR1 (Vellayani) was more virulent among rice isolates. t among rice isolates.t among rice isolates. t among rice isolates.t among rice isolates. t among rice isolates.t among rice isolates.t among rice isolates. t among rice isolates. t among rice isolates. Among cowpea isolates, KRC1 (Kottarakkara) was more virulent. TRA2 (Isolate from Chirayinkeezh) was more virulent among amaranth R. solani isolates. Various cultural characters like colony colour, pigmentation, rate of growth, texture of growth, days for sclerotial initiation, zonation, growth margin, dry weight of mycelium were studied for the different isolates and variations were observed among isolates. All isolates from rice and cowpea; and TRA2 (Chirayinkeezh), PRA1(Ranni) from amaranth were fast growers. Rate of growth was high in KRR1 (Kottarakkara), PRC2 (Thiruvalla) and PRA1 (Ranni) collected from rice, cowpea and amaranth respectively in PDA medium compared to other isolates. All R. solani isolates of amaranth and two cowpea isolates -TRC1 (Vellayani) and KRC2 (Pooyapally) didn‟t produce sclerotia in the culture. Zonation was absent in all rice and cowpea isolates except TRC1 (Vellayani) where a slight zonation was present. Days for initiation of sclerotial production ranged from 3 to 4 days. Pathogen was highly variable in microscopic and sclerotial characters. Mean hyphal width varies from 3.81 μm (TRR2) to 6.95 μm (PRR2). Isolates show variation in the shape of moniliod cells which is the histological change of hyphae formed in the culture. A noticeable variation could be seen in sclerotial characters like colour, size, texture, shape, number, weight, orientation, position and clump formation. Macroscopic vegetative compatibility reaction between isolates of R. solani are merge, merging line, tuft, barrage, barrage line and microscopic hyphal anastmosis reaction are C0, C1, C2 and C3. Out of the 171 culture combinations, merge reactions and C2 hyphal anastomosis were most commonly found. There was less hyphal anastomosis reaction between amaranth and rice R. solani isolates and between amaranth and cowpea R. solani isolates(C0). More hyphal anastomosis reactions are present between rice and cowpea isolates and also within the same hosts (C2 and C3). C3 reaction is vegetatively compatible and C0, C1 and C2 reactions are vegetatively incompatible reactions. Pathogenic variability among the isolates was analysed on Arun variety of amaranth. All R. solani isolates from rice, cowpea and amaranth were found infecting amaranth whereas variations in variations in variations in variations in variations in degree of pathogenicity were observed among isolates. PRR2 (Thiruvalla, PDI -46.66%), PRC1 (Ranni, PDI - 58.33%) and PRA1 (Ranni, PDI -55.55%), were found most virulent among rice, cowpea and amaranth isolates respectively. Among all isolates PRC1 (Ranni) was the most virulent on amaranth. Genetic variability was analyzed through Random Amplified Polymorphic DNA (RAPD) using four random primers such as OPW-13, OPA-04, OPA-19, OPA-20. The primers were found very informative in generating high level of polymorphism in the RAPD electrophoretic banding pattern. Intraspecific variability of R. solani isolates was expressed among the population from different as well as from same geographical regions. R. solani isolated from amaranth plant does not produced sclerotia in the culture. All R. solani isolates produced symptoms on amaranth plant. Microscopic, microscopic characters and virulence were not affected in geographical origin. No correlation found between virulence and cultural and morphologic characters. Intra specific variability among the population from the same and different geographical regions expressed through RAPD analysis. The study reveals that the isolates are cross infective between crops. The variation is observed at morphological, cultural and molecular level. This will help in developing suitable management practices. The specific gene responsible for the variation in R. solani should be identified. Avirulent strain can be developed as biocontrol agent for the future disease management.